The Impact of Clinical Pharmacy Services in a Tertiary Care Center Specialized in Pediatric Hemato-Oncology - Christina Gradwohl; Gernot Engstler; Martina Anditsch; Herbert Pichler; Gunar Stemer (MDPI AG, 2022)
Clinical pharmacy services (CPS) have shown beneficial effects on several outcome measures in hospital patients, including the reduction of drug-related problems (DRP) and of therapy costs. Less is known about the impact of CPS in pediatric haemato-oncology, even though this patient population is highly susceptible to DRP. CPS were implemented in a tertiary care children's hospital specialized in hemato-oncology and hematopoietic stem cell transplantation. The main outcome measures were type and number of DRP, type and number of pharmaceutical interventions (PI), their acceptance rate, and their clinical significance and economic benefit. During 6 months and 32 ward rounds, 275 DRP were identified and addressed by PI. The acceptance of PI was high (73.4%), and up to 80% of PI were rated as very significant or significant by independent external raters. The estimated therapy cost reductions were substantial, approaching at least EUR 54,600 for avoided follow-up costs. Conclusion: CPS improve medication safety in pediatric hemato-oncology and may reduce therapy costs.